Lack of TNF‐alpha receptor type 2 protects motor neurons in a cellular model of amyotrophic lateral sclerosis and in mutant SOD1 mice but does not affect disease progression. (4th June 2015) - Tortarolo, Massimo; Vallarola, Antonio; Lidonnici, Dario; Battaglia, Elisa; Gensano, Francesco; Spaltro, Gabriella; Fiordaliso, Fabio; Corbelli, Alessandro; Garetto, Stefano; Martini, Elisa; Pasetto, Laura; Kallikourdis, Marinos; et al.
Abstract: Changes in the homeostasis of tumor necrosis factor α (TNFα) have been demonstrated in patients and experimental models of amyotrophic lateral sclerosis (ALS). However, the contribution of TNFα to the development of ALS is still debated. TNFα is expressed by glia and neurons and acts through the membrane receptors TNFR1 and TNFR2, which may have opposite effects in neurodegeneration. We investigated the role of TNFα and its receptors in the selective motor neuron death in ALS in vitro and in vivo . TNFR2 expressed by astrocytes and neurons, but not TNFR1, was implicated in motor neuron loss in primary SOD1‐G93A co‐cultures. Deleting TNFR2 from SOD1‐G93A mice, there was partial but significant protection of spinal motor neurons, sciatic nerves, and tibialis muscles. However, no improvement of motor impairment or survival was observed. Since the sciatic nerves of SOD1‐G93A/TNFR2−/− mice showed high phospho‐TAR DNA‐binding protein 43 (TDP‐43) accumulation and low levels of acetyl‐tubulin, two indices of axonal dysfunction, the lack of symptom improvement in these mice might be due to impaired function of rescued motor neurons. These results indicate the interaction between TNFR2 and membrane‐bound TNFα as an innovative pathway involved in motor neuron death. Nevertheless, its inhibition is not sufficient to stop disease progression in ALS mice, underlining the complexity of this pathology. We show evidence of the involvement of neuronal and astroglial TNFR2 in the motor neuron degeneration in ALS. Both concur to cause motor neuron death in primary astrocyte/spinal neuron co‐cultures. TNFR2 deletion partially protects motor neurons and sciatic nerves in SOD1‐G93A mice but does not improve their symptoms and survival. However, TNFR2 could be a new target for multi‐intervention therapies. Abstract : We show evidence of the involvement of neuronal and astroglial TNFR2 in the motor neuron degeneration in ALS. Both concur to cause motor neuron death in primary astrocyte/spinal neuron co‐cultures. TNFR2 deletion partially protects motor neurons and sciatic nerves in SOD1‐G93A mice but does not improve their symptoms and survival. However, TNFR2 could be a new target for multi‐intervention therapies. Cover Image for this issue: doi:10.1111/jnc.12905 .